PERSEPSI SISWA SEKOLAH MENENGAH PERTAMA TERHADAP CERITA RAKYAT MUNA - NFN Mulawati (Balai Bahasa Sulawesi Tengah, 2013)
Munanese community in Sulawesi Tenggara also have their own traditional literature. This traditional literature have two types, they are prose and poems. Oral tradition which include as prose are legend, fairy tale, fable, myth, and sage. The existing of this oral tradition is almost disappear. This was caused by the attention of young generation is less day by day. Beside that, some old people that know this oral tradition is difficult to find. Nowdays, oral tradition is changed by modern literature which can be found in every mass media. La Kimi Batoa wrote in his article tittled Munanese Oral Tradition which contained with some Munanese poems. This article try to discuss the relationship between local literature and its community. The writer will discuss students attitude ofSMP toward Munanese folktale. The objective of this discussion is to describe the attitude of SMP student toward Munanese folktale.